Social and economic value of Portuguese community pharmacies in health care - Jorge Félix; Diana Ferreira; Marta Afonso-Silva; Marta Vargas Gomes; César Ferreira; Björn Vandewalle; Sara Marques; Melina Mota; Suzete Costa; Maria Cary; Inês Teixeira; Ema Paulino; et al. (BMC Health Services Research, 2017)
Abstract Background Community pharmacies are major contributors to health care systems across the world. Several studies have been conducted to evaluate community pharmacies services in health care. The purpose of this study was to estimate the social and economic benefits of current and potential future community pharmacies services provided by pharmacists in health care in Portugal. Methods The social and economic value of community pharmacies services was estimated through a decision-model. Model inputs included effectiveness data, quality of life (QoL) and health resource consumption, obtained though literature review and adapted to Portuguese reality by an expert panel. The estimated economic value was the result of non-remunerated pharmaceutical services plus health resource consumption potentially avoided. Social and economic value of community pharmacies services derives from the comparison of two scenarios: “with service” versus “without service”. Results It is estimated that current community pharmacies services in Portugal provide a gain in QoL of 8.3% and an economic value of 879.6 million euros (M€), including 342.1 M€ in non-remunerated pharmaceutical services and 448.1 M€ in avoided expense with health resource consumption. Potential future community pharmacies services may provide an additional increase of 6.9% in QoL and be associated with an economic value of 144.8 M€: 120.3 M€ in non-remunerated services and 24.5 M€ in potential savings with health resource consumption. Conclusions Community pharmacies services provide considerable benefit in QoL and economic value. An increase range of services including a greater integration in primary and secondary care, among other transversal services, may add further social and economic value to the society.